Design and Development of a Web-Based Library Application for Sawah Subdistrict, South Tangerang - Safudin, Mahmud; Setiaji, Setiaji (Sean Institute, 2025)
The rapid advancement of information technology has encouraged public service institutions, including libraries, to adopt digital systems to enhance service efficiency and accessibility. This study aims to design and implement a web-based library information system for the Sawah Subdistrict Office in South Tangerang. The research employs the System Development Life Cycle with the Waterfall model, covering stages of requirement analysis, system design, coding, and testing. Data were obtained through field observations, interviews, and literature reviews. The developed system enables library staff to manage book collections, member data, and loan transactions more efficiently, while allowing users to access real-time information on book availability. The implementation of the system improves data accuracy, expands service reach, and facilitates automatic report generation. The findings demonstrate that integrating a web-based system into library management can optimize operations, enhance transparency, and provide better services to the community.